Analysis of parking usage at the park and ride facility in Klang Valley, Malaysia - Kadar Hamsa, Abdul Azeez; Syed Adnan, Sharifah Adibah Alyia; Khalid, Ummi Aqilah (WIT Press, 2014)
A parking utilization survey was administered to examine the parking usage at three selected park and ride facilities along the Kelana Jaya LRT Line and Putrajaya Public transportation terminal (Putrajaya Sentral). This study also analyses the existing parking supply and its physical conditions through a parking space inventory survey at the three selected facilities. Parking characteristics such as parking occupancy, parking accumulation, parking turnover and parking duration at each facility were also examined. Findings showed that overall parking utilization pattern was generally high with the occupancy rate of more than 85% (Terminal Putra station) and more than 92% (Kelana Jaya station). However, the Putrajaya Sentral park and ride facility recorded low occupancy rate at multi-storey parking (below 50%) but high occupancy rate at surface parking (85%). Additionally, all park and ride stations were used by long-term parkers (more than 7 hours). The results from this study were found to be comparable with park and ride studies at Shah Alam and Seremban KTM stations and Washington. A high parking demand at the park and ride facility will, eventually, help to achieve the benefits of sustainable transportation. Finally, recommendations to improve parking supply to meet increase in parking demand and conclusions are also drawn.